“JUKEBOX SERVICES”®: A TYPOLOGY FOR THE PROVISION OF SERVICE - Odyssefs Kollias (European Scientific Journal, ESJ, 2014)
“Jukebox services”®*, is a new typology* related to the provision* of services. It is an attempt to define and describe accurately and sharply an attitude which can be met at service. This typology defines the “fake” servicing diathesis which is demonstrated by some service providers who provide proper service only when they are getting paid or they are getting a tip. “Jukebox service”® refers to the situation when a service representative does not provide what the Services Marketing science describes as a proper service but, whose sole drive in servicing is to receive money from his customer rather than satisfying him. Thus, this service is considered fake because it is not customer oriented. “Jukebox services”® can be met in many industries, even to public sector services.